SYNAPTOTAGMIN 4 is expressed mainly in the phloem and participates in abiotic stress tolerance in Arabidopsis - Kumar, Ajay; Krausko, Miroslav; Jásik, Ján (Frontiers in Plant Science, 2024)
Plant synaptotagmins structurally resemble animal synaptotagmins and extended-synaptotagmins. Animal synaptotagmins are well-characterized calcium sensors in membrane trafficking, and extended-synaptotagmins mediate lipid transfer at the endoplasmic reticulum-plasma membrane contact sites. Here, we characterize SYNAPTOTAGMIN 4 (SYT4), which belongs to the six-member family in Arabidopsis. Fluorometric GUS assay showed that the SYT4 promoter was strongest in roots and the least active in rosettes and cauline leaves, which was confirmed by qPCR. In seedlings, promoter activity was influenced by several factors, such as plant growth regulators, mannitol, sucrose, polyethylene glycol and cold. GUS histochemistry revealed SYT4 promoter activity in the phloem of all organs and even almost exclusively in sieve element precursors and differentiating sieve elements. Accordingly, the SYT-GFP fusion protein also accumulated in these cells with maximal abundance in sieve element precursors. The protein formed a network in the cytoplasm, but during sieve tube differentiation, it deposited at the cell periphery and disappeared from mature tubes. Using photoconvertible fluorescence technology, we showed that a high abundance of SYT4 protein in meristematic protophloem cells was due to its extensive synthesis. SYT4 protein synthesis was interrupted in differentiating sieve elements, but protein degradation was also reduced. In addition to phloem, the fusion protein was detected in shoot and root stem cell niche as early as the late heart stage of the embryo. We isolated and molecularly biologically characterized five syt4 T-DNA insertion alleles and subjected them to phenotype analysis. The allele with the C2B domain interrupted by an insertion exhibits increased sensitivity to factors such as auxins, osmotics, salicylic acid, sodium chloride, and the absence of sucrose in the root growth test.